UCS551 - Introduction to Data Analytics And Application / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA, 2021)
This course is an introductory course on data analytics and its application, which include basic data management, methods to explore and visualize data effectively; as well as classification and data clustering using selected machine learning techniques. During the course, the techniques will be illustrated using a range of data and case studies with respect to the study program.